Policymaking, Ideational Power and the Role of the Media. (May 2022) - Curran, Declan; Gillanders, Robert; Mahmalat, Mounir
The ideational power framework developed by Carstensen and Schmidt has sought to make explicit the manner in which ideas can exert an influence over policy outcomes. However, one key feature of this theoretical framework has not yet been adequately conceptualised: the communicative process through which policy entrepreneurs convey their ideas to the general public. This article focuses on one specific form of communicative discourse as a means of generating widespread public support for a given policy proposal: public discourse via the media – be it print, broadcast or social media. We argue that the ideational power literature should recognise the media as a powerful entity in its own right rather than merely depicting the media as an implement for political communication. We contend that the ideational power framework could usefully incorporate a characterisation of the media that has recently emerged from political communications research: the hybrid media system. In order to illustrate how the communicative process inherent in ideational power can be understood in terms of a hybrid media system, we undertake a comparative review of two empirical studies which assess political discourse during the 2016 US presidential election from the perspectives of ideational power and hybrid media systems.